A eutectic lithium-ion battery electrolyte based on molecular plastic crystal and its preparation method and application
By using the specific ratio of molecular crystallization additives to the electrolyte lithium salt in lithium ion battery electrolyte, a low eutectic electrolyte is prepared, which solves the problem of unstable operation of the electrolyte under wide temperature conditions and realizes the battery's further operation Stable operation and safety improvement in the wide temperature range.
Patent Information
- Application Number
- CN202410912107.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-07-09
AI Technical Summary
The existing lithium-ion battery electrolyte cannot operate normally under wide temperature conditions. The electrolyte fluidity decreases and may solidify at low temperatures, and may decompose at high temperatures, resulting in unstable battery operation and safety hazards.
Using a low-eutectic lithium-ion battery electrolyte based on molecular plastic crystallization, by combining molecular plastic crystallization additives (such as 2-methylimidazole, neopentyl glycol, etc.) with electrolyte lithium salts (such as lithium bistrifluoromethanesulfonimide etc.) Mix at a specific molar ratio to prepare an electrolyte with low eutectic properties.
The eutectic electrolyte has no melting peaks and solidification peaks during heating-cooling from -100℃ to 150℃, and only glass transition occurs, with high thermal stability, and can avoid solidification under low temperature conditions. Avoid decomposition and broaden the service temperature range of lithium-ion batteries.
Smart Images

Figure CN118645690B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a low-melting lithium ion battery electrolyte based on molecular crystal molding, and a preparation method and application thereof. Background Art
[0002] At present, lithium-ion batteries have unique advantages in the field of new energy due to their high voltage, large specific capacity and long cycle life. They are currently the most widely used power and energy storage power source. Although the application scenarios of lithium-ion batteries are already very extensive, my country has a vast territory and rapid technological progress, and the application scenarios of lithium-ion batteries have been further expanded. Therefore, the development of a "wide temperature range" lithium-ion battery that can serve under high temperature (>100℃) and low temperature (-40℃) working conditions has attracted widespread attention.
[0003] As one of the key materials that make up the battery, the electrolyte plays the role of ion conduction and battery protection. While transmitting lithium ions, it can also prevent the battery from overheating, overvoltage, overcharging and other adverse conditions when working, so as to ensure the normal operation of the battery. However, when operating at low temperatures, the fluidity of the electrolyte will decrease; when the working environment temperature drops below the melting point, the electrolyte will also solidify, which will reduce the working efficiency and cause greater safety hazards to the battery operation. Operating at high temperatures will cause side reactions in the electrolyte, and decomposition will occur when the electrolyte decomposition temperature is higher than the decomposition temperature, which is also not conducive to the normal operation of the battery.
[0004] As an important task of battery modification in electrochemistry, electrolyte engineering has proposed new concepts of high-safety electrolytes such as solid electrolytes, ionic liquids, high-concentration electrolytes, and low-eutectic electrolytes, which have great development potential in the application field of batteries over a wide temperature range. Summary of the invention
[0005] The purpose of the present invention is to provide a low-melting lithium-ion battery electrolyte based on molecular crystal molding and a preparation method and application thereof, so as to solve the problem that the existing electrolyte cannot serve under wide temperature conditions.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a low-melting lithium-ion battery electrolyte based on molecular crystal shaping, comprising the following raw materials in molar fractions: 40-80% of a molecular crystal shaping additive and 60-20% of an electrolyte lithium salt;
[0008] The molecular crystal shaping additive is 2-methylimidazole, neopentyl glycol, 2-amino-2-methyl-1,3-propanediol, 2-hydroxymethyl-1,3-propanediol, 2-hydroxymethyl-2-methyl-1,3-propanediol, 2-ethyl-2-(hydroxymethyl)-1,3-propanediol, tris(hydroxymethyl)aminomethane or pentaerythritol.
[0009] Preferably, in the low-melting eutectic lithium-ion battery electrolyte based on molecular crystal shaping, the electrolyte lithium salt is lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide or lithium bis(perfluoroethanesulfonyl)imide.
[0010] Preferably, in the low-melting eutectic lithium-ion battery electrolyte based on molecular crystal shaping, the molar fraction of the molecular crystal shaping additive is 60-80%, and the molar fraction of the electrolyte lithium salt is 40-20%.
[0011] The present invention also provides a method for preparing a eutectic lithium-ion battery electrolyte based on molecular crystal molding, comprising the following steps:
[0012] The molecular crystal shaping additive is mixed with the electrolyte lithium salt to obtain a low-melting lithium-ion battery electrolyte based on molecular crystal shaping.
[0013] Preferably, in the method for preparing the low-melting eutectic lithium-ion battery electrolyte based on molecular crystal shaping, the mixing is specifically mixing under oil bath conditions.
[0014] Preferably, in the method for preparing the low-melting eutectic lithium-ion battery electrolyte based on molecular crystal molding, the mixing temperature is 70 to 85° C., and the mixing time is 40 to 50 minutes.
[0015] Preferably, in the method for preparing the low-melting eutectic lithium-ion battery electrolyte based on molecular crystal molding, the mixing stirring speed is 100 to 600 rpm.
[0016] The present invention also provides an application of a low-melting lithium-ion battery electrolyte based on molecular crystal molding in a lithium-ion battery. The application temperature range of the low-melting lithium-ion battery electrolyte based on molecular crystal molding is -76 to 163°C.
[0017] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) The raw material selection (molecular plasticizer and electrolyte lithium salt) and their molar ratio and synthesis process parameters of the present invention are not disclosed in the existing electrolyte related technology;
[0019] (2) The eutectic electrolyte obtained by the present invention has the following characteristics: ① Compared with pure substances, the eutectic electrolyte of the present invention has no melting peak and solidification peak when heated and cooled at -100℃~150℃, only glass transition occurs, and the physical phase existence state is relatively stable; ② Extremely low glass transition temperature; ③ High thermal stability. The above characteristics can prevent the electrolyte from solidifying when the lithium-ion battery works under low temperature conditions, and prevent the electrolyte from decomposing when working under higher temperature conditions, and still maintain a certain service capacity, which can broaden the service temperature range of the corresponding lithium-ion battery;
[0020] (3) In the present invention, the thermal stability of the components plays a decisive role in the thermal stability of the electrolyte. Among the raw materials used, lithium bis(trifluoromethanesulfonyl)imide has the best temperature stability. After being mixed with molecular plastic alcohols and their derivatives or 2-methylimidazole to prepare an electrolyte, the overall weakening of the interaction force between the system molecules and the increase in the system entropy lead to the low eutectic effect. The thermal stability of the electrolyte is improved compared with the stability of alcohols and their derivatives or 2-methylimidazole.
[0021] (4) After the low-melting electrolyte prepared by the present invention introduces alcohol and its derivatives or 2-methylimidazole, the preparation cost of the electrolyte can be reduced to a certain extent due to the relatively cheap raw material price. At the same time, it also has the advantages of simple preparation process, non-flammability and non-volatility;
[0022] (5) The electrolyte lithium salt of the present invention can be replaced by other electrolyte metal salts, and can be further expanded to corresponding metal batteries or metal ion batteries, such as sodium, potassium, magnesium, aluminum, iron, zinc, calcium, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.
[0024] Figure 1 The invention provides a process for preparing the eutectic lithium-ion battery electrolyte.
[0025] Figure 2 The preparation process of the eutectic lithium ion battery electrolyte of Examples 1 to 2;
[0026] Figure 3 The differential scanning calorimetry (DSC) test results of the three raw materials and the eutectic lithium ion battery electrolyte of Examples 1 to 2;
[0027] Figure 4Thermogravimetric analysis (TG) test results of three raw materials and eutectic lithium ion battery electrolytes of Examples 1 and 2; (a) is the TG curve of the eutectic lithium ion battery electrolyte and its raw materials of Example 1, and (b) is the TG curve of the eutectic lithium ion battery electrolyte and its raw materials of Example 2;
[0028] Figure 5 The appearance of the eutectic lithium-ion battery electrolyte of three raw materials and Examples 1 to 2 at room temperature;
[0029] Figure 6 The conductivity test results of the eutectic lithium-ion battery electrolyte of Examples 1 to 2 from 25° C. to 80° C.;
[0030] Figure 7 This is a combustion experiment of the eutectic lithium-ion battery electrolyte of Examples 1 and 2. DETAILED DESCRIPTION
[0031] The present invention provides a low-melting lithium-ion battery electrolyte based on molecular crystal shaping, comprising the following raw materials in molar fractions: 40-80% of a molecular crystal shaping additive and 60-20% of an electrolyte lithium salt;
[0032] The molecular crystal shaping additive is 2-methylimidazole, neopentyl glycol, 2-amino-2-methyl-1,3-propanediol, 2-hydroxymethyl-1,3-propanediol, 2-hydroxymethyl-2-methyl-1,3-propanediol, 2-ethyl-2-(hydroxymethyl)-1,3-propanediol, tris(hydroxymethyl)aminomethane or pentaerythritol.
[0033] In the present invention, the molecular crystal shaping additive is preferably 2-methylimidazole, neopentyl glycol, 2-amino-2-methyl-1,3-propanediol, 2-hydroxymethyl-1,3-propanediol, tris(hydroxymethyl)aminomethane or pentaerythritol, further preferably 2-methylimidazole, neopentyl glycol, tris(hydroxymethyl)aminomethane or pentaerythritol, more preferably 2-methylimidazole or neopentyl glycol.
[0034] In the present invention, the electrolyte lithium salt is preferably lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide or lithium bis(perfluoroethanesulfonyl)imide, more preferably lithium bis(fluorosulfonyl)imide or lithium bis(trifluoromethanesulfonyl)imide, and more preferably lithium bis(trifluoromethanesulfonyl)imide.
[0035] In the present invention, the molar fraction of the molecular crystal shaping additive is 40 to 80%, preferably 60 to 80%, and more preferably 70 to 80%.
[0036] In the present invention, the molar fraction of the electrolyte lithium salt is 60 to 20%, preferably 40 to 20%, and more preferably 30 to 20%.
[0037] The present invention also provides a method for preparing a eutectic lithium-ion battery electrolyte based on molecular crystal molding, comprising the following steps:
[0038] The molecular crystal shaping additive is mixed with electrolyte lithium salt to obtain a low-melting lithium-ion battery electrolyte.
[0039] In the present invention, the mixing is preferably carried out under oil bath conditions.
[0040] In the present invention, the mixing is preferably carried out under magnetic stirring.
[0041] In the present invention, the mixing temperature is preferably 70 to 85° C.; the mixing time is preferably 40 to 50 min.
[0042] In the present invention, the stirring speed of the mixing is preferably 100 to 600 rpm, more preferably 200 to 400 rpm, and even more preferably 300 rpm.
[0043] The present invention also provides an application of a low-melting lithium-ion battery electrolyte based on molecular crystal molding in a lithium-ion battery. The application temperature of the low-melting lithium-ion battery electrolyte based on molecular crystal molding is preferably -76 to 163°C.
[0044] The low eutectic lithium ion battery electrolyte of the present invention can be used above the glass transition temperature and has a wider application temperature range.
[0045] The preparation process of the eutectic lithium ion battery electrolyte of the present invention is as follows Figure 1 As shown, it includes: ratio calculation → sample weighing → sample mixing → oil bath heating + magnetic stirring → natural cooling.
[0046] The preparation principle of the eutectic electrolyte is: Lewis or Bronsted acid and base are mixed in appropriate proportions, and the acid and base act as donors or acceptors of hydrogen bonds or lithium bonds. Due to the overall weakening of the interaction between the molecules in the system and the increase in the system entropy, according to the Gibbs free energy criterion, the melting point of the mixed system is significantly reduced, and at the eutectic component, the melting point reaches a minimum, and the eutectic phenomenon occurs.
[0047] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Example 1
[0049] This embodiment provides a method for preparing a eutectic lithium-ion battery electrolyte based on molecular crystal molding, comprising the following steps:
[0050] Weigh 2-methylimidazole (2-MIm) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) with a weighing accuracy of 0.01 mg; mix 80% mol% 2-methylimidazole and 20% mol% lithium bis(trifluoromethanesulfonyl)imide at room temperature, mix the mixture in an oil bath at 85° C. and under magnetic stirring at 300 rpm for 40 min, and cool naturally to room temperature to obtain a low-melting lithium-ion battery electrolyte based on molecular plastic crystal, which is recorded as 2-MIm+LiTFSI. The preparation process is as follows: Figure 2 shown.
[0051] Example 2
[0052] This embodiment provides a method for preparing a eutectic lithium-ion battery electrolyte based on molecular crystal molding, comprising the following steps:
[0053] Neopentyl glycol (NPG) and lithium bis(trifluoromethanesulfonyl)imide were weighed with a weighing accuracy of 0.01 mg; 70% mole fraction of neopentyl glycol and 30% mole fraction of lithium bis(trifluoromethanesulfonyl)imide were mixed at room temperature, the mixed sample was mixed for 40 minutes under 70° C. oil bath conditions and 300 rpm magnetic stirring, and naturally cooled to room temperature to obtain a low-melting lithium-ion battery electrolyte based on molecular plastic crystal, which was recorded as NPG+LiTFSI. The preparation process is as follows: Figure 2 shown.
[0054] For the three raw materials involved in the present invention and the eutectic lithium ion battery electrolyte prepared in Examples 1 to 2, DSC test was performed using the test conditions in Table 1 to obtain the phase change point (freezing point, melting point), glass transition temperature T g The results are as follows Figure 3 shown.
[0055] Depend on Figure 3 It can be seen that:
[0056] (1) The pure substances 2-MIm, NPG, LiTFSI and the like involved in the present invention all show sharp melting peaks when heated, indicating that a melting phase transition occurs and undergoes a solid-to-liquid phase transition process; the melting points of the three are all over 120°C; in addition, 2-MIm, NPG and LiTFSI all have additional endothermic peaks before melting, indicating that they all have a certain degree of plastic crystal properties;
[0057] (2) During the temperature rise test, the melting peaks of the two electrolytes prepared in Examples 1 to 2 of the present invention disappeared, and only glass transition occurred, indicating that the aggregation state of the electrolyte did not change significantly within the entire test temperature range;
[0058] (3) The glass transition of the two electrolytes prepared in Examples 1 and 2 of the present invention is both carried out at a temperature below -40°C, which is beneficial for the battery to serve under low temperature conditions.
[0059] Table 1. DSC test conditions of the eutectic lithium-ion battery electrolyte prepared by three raw materials and Examples 1 to 2
[0060]
[0061] The mass change parameters of a substance during heating can be obtained by variable temperature thermogravimetric analysis (TG) testing. The conditions of the TG test are: temperature range 30-500°C, heating rate 10°C / min, carrier gas N2, carrier gas flow rate 50mL / min, and all sampling masses are 5mg. The thermal stability related parameters of the substance (such as Figure 4 and Table 2).
[0062] Depend on Figure 4 From Table 2, we can see that:
[0063] (1) The pure substances of 2-MIm, NPG, and LiTFSI lose weight upon heating, and there is only one evaporation or decomposition step; the electrolyte prepared in Examples 1 to 2 loses weight upon heating with two steps because it contains two components, and the two components interact with each other through non-covalent bonds such as lithium bonds and hydrogen bonds;
[0064] (2) The initial decomposition temperatures of the electrolytes prepared in Examples 1 to 2 are all >135° C., indicating that the eutectic electrolyte prepared in the present invention has good thermal stability and can meet the service performance requirements under higher temperature conditions.
[0065] Table 2. TG test results of eutectic lithium-ion battery electrolytes prepared from three raw materials and Examples 1 to 2
[0066]
[0067] Application Examples
[0068] The eutectic lithium ion battery electrolyte (such as Figure 5 As shown) are respectively tested for ionic conductivity. The test method is: using the "stainless steel sheet | electrolyte | stainless steel sheet" battery structure for testing, loading a polytetrafluoroethylene gasket between the two steel sheets, the gasket inner diameter is 10mm, and the thickness is 1.5mm; the inside of the gasket is respectively dripped with the electrolyte to be tested in Example 1 or 2, and the loading process is completed in the glove box; using a constant temperature bath with a temperature control accuracy of ±0.01°C for heating, the test temperature range is 25 to 80°C, and a measurement point is taken every 5°C. An Autolab electrochemical workstation is used for ionic conductivity testing, and the electrochemical impedance spectroscopy (EIS) test parameters are 1MHz to 1Hz.
[0069] The ionic conductivity calculation formula is: σ=d / (Z×S); wherein d is the thickness of the polytetrafluoroethylene gasket, Z is the intersection of the impedance spectrum and the real axis in the Nyquist plot (or the resistance value obtained by fitting an equivalent circuit), and S is the area of the polytetrafluoroethylene gasket hole.
[0070] The ionic conductivity test results of the eutectic lithium ion battery electrolyte obtained in Examples 1 to 2 are shown in Tables 3, 4 and Figure 6 As shown. Among them, Table 3 and Table 4 respectively give the ionic conductivity of Examples 1 and 2 from low temperature to high temperature in the temperature range of 25 to 80°C. Obviously, the ionic conductivity of Example 1 is slightly lower than that of Example 2, and as the temperature increases, the ionic conductivity values of both increase, indicating that they have a strong temperature dependence. In addition, the reason why the conductivity of Example 2 is higher than that of Example 1 may be that NPG has more lithium bond acceptors and hydrogen bond donors than 2-MIm.
[0071] Table 3. Ionic conductivity test results of the eutectic lithium ion battery electrolyte of Example 1
[0072] Temperature / ℃ Conductivity / (mS / cm) Temperature / ℃ Conductivity / (mS / cm) 25 0.056 55 0.450 30 0.080 60 0.592 35 0.121 65 0.771 40 0.174 70 0.979 45 0.243 75 1.224 50 0.335 80 1.497
[0073] Table 4. Ionic conductivity test results of the eutectic lithium ion battery electrolyte of Example 2
[0074] Temperature / ℃ Conductivity / (mS / cm) Temperature / ℃ Conductivity / (mS / cm) 25 0.116 55 0.673 30 0.157 60 0.867 35 0.225 65 1.099 40 0.300 70 1.382 45 0.400 75 1.690 50 0.530 80 2.078
[0075] In addition, by Figure 7 It can be seen from the combustion experiment that the electrolytes of Examples 1 and 2 did not burn after being ignited for 10 seconds and 2 seconds respectively, proving that the low-eutectic lithium-ion battery electrolytes of Examples 1 and 2 are both non-flammable or non-flammable.
[0076] The above is only a preferred embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention.
Claims
1. A eutectic lithium-ion battery electrolyte based on molecular plastic crystal, characterized in that: The invention is composed of the following raw materials in molar fractions: 40-80% of molecular plastic crystal additive and 60-20% of electrolyte lithium salt; The molecular crystal shaping additive is 2-methylimidazole or neopentyl glycol; The electrolyte lithium salt is lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide or lithium bis(perfluoroethanesulfonyl)imide.
2. The eutectic lithium-ion battery electrolyte based on molecular plastic crystal according to claim 1, characterized in that: The molar fraction of the molecular plastic crystal additive is 60-80%, and the molar fraction of the electrolyte lithium salt is 40-20%.
3. The method for preparing a eutectic lithium-ion battery electrolyte based on molecular crystal shaping according to claim 1 or 2, characterized in that: The following steps are involved: The molecular crystal shaping additive is mixed with the electrolyte lithium salt to obtain a low-melting lithium-ion battery electrolyte based on molecular crystal shaping.
4. The method for preparing a eutectic lithium-ion battery electrolyte based on molecular crystal shaping according to claim 3, characterized in that: The mixing is specifically mixing under oil bath conditions.
5. The method for preparing a eutectic lithium-ion battery electrolyte based on molecular crystal shaping according to claim 3 or 4, characterized in that: The mixing temperature is 70-85° C., and the mixing time is 40-50 min.
6. The method for preparing a eutectic lithium-ion battery electrolyte based on molecular crystal shaping according to claim 5, characterized in that: The stirring speed of the mixing is 100-600 rpm.
7. Use of the eutectic lithium ion battery electrolyte based on molecular crystallization according to any one of claims 1 to 2 or the method for preparing the eutectic lithium ion battery electrolyte based on molecular crystallization according to any one of claims 3 to 6 in lithium ion batteries, characterized in that: The temperature range of application of the molecular plastic crystal-based eutectic lithium-ion battery electrolyte is -76 to 163°C.
Citation Information
Patent Citations
Non-aqueous cell liquor and lithium secondary battery containing it
CN1531134A
Organic electrolyte solution for lithium ion secondary batteries, and lithium ion secondary battery
WO2015182716A1